Socio-cultural interpretation of the phenomenon of old age in Shakespeare‘s tragedy King Lear - Andrejević, Ana (Sociološki pregled, 2022)
The focus of the research in this paper is socio-cultural interpretation of the phenomenon of old age and intergenerational conflict with the literary projection in King Lear. The study of the socio-historical context in which the play was written is focused on the renaissance interpretation of old age and equation of the representatives of this age group with the remainder of the feudal system at the moment of the awakening of individualism and the beginning of capitalism. The interdisciplinary approach has been applied in the research, while the basic theoretical framework of the paper is composed of the theses of the sociology of literature and theatre, literary methods of new historicism, as well as gerontology, the psychology of getting older, and sociology of the family. The main hypothesis considered in the paper is that this Shakespeare‘s tragedy reflects the social reality of the late renaissance era, including the marginalized position of old age. The obtained results show intolerance of the social environment towards old persons and the subversive character of younger generations that often express gerontophobia, which is in favour the classification of King Lear as a geriatric tragedy.
Keywords: old age; intergenerational conflict; family; Renaissance; Shakespeare